Multi-layered based network security defense system (Tongxin xuebao)
A multi-layered based network security defense system（MNSDS） was presented.MNSDS adopts multi-layered detection technology: for the detection of IP layer,aggregate-based congestion control algorithm（ABCC） was adopted,narrowing the congestion signature,and thus minimizing collateral damage;then,it employs the detection technology based on the artificial immune principle in TCP and UDP layers AIPT,and detects intrusion by creating a rule database and matching the appropriate rule.The simulation results indicate that the system not only can provide relief from DoS/DDoS attacks equally,but also resolve problems existing in the current defense systems such as low speed high false positive probability and high false positive probability,poor real-time and more artificial interventions.